Analysis of document-mining techniques and tools for technology intelligence: discovering knowledge from technical documents. (2012) - Lee, Sungjoo; Mortara, Letizia; Kerr, Clive; Phaal, Robert; Probert, David
This research proposes a method for extracting technology intelligence (TI) systematically from a large set of document data. To do this, the internal and external sources in the form of documents, which might be valuable for TI, are first identified. Then the existing techniques and software systems applicable to document analysis are examined. Finally, based on the reviews, a document-mining framework designed for TI is suggested and guidelines for software selection are proposed. The research output is expected to support intelligence operatives in finding suitable techniques and software systems for getting value from document-mining and thus facilitate effective knowledge management.